(untitled) (INTERNATIONAL SEMINAR, 2024)
This study investigates the impact of artificial intelligence (AI) on students’ English writing proficiency within the context of language learning. As AI tools become increasingly integrated into educational settings, they offer unique opportunities for enhancing writing skills through immediate feedback, personalized learning experiences, and increased engagement. This research identifies both the benefits and challenges associated with AI usage, including the risk of over-reliance on technology, potential inaccuracies in AI-generated suggestions, and the digital divide that may affect access to these resources. Furthermore, the study explores how the integration of AI alters teaching practices and the role of educators in fostering writing proficiency. The findings highlight the need for a balanced approach that combines AI tools with traditional instructional methods to optimize student learning outcomes.